2015
DOI: 10.1039/c5cc02570b
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of bioactive multilayered nanocoatings on pancreatic islet cells: incorporation of α1-antitrypsin into the coatings

Abstract: A spontaneous multilayer deposition approach for presenting therapeutic proteins onto pancreatic islet surfaces, using a heparin polyaldehyde and glycol chitosan alternating layering scheme, has been developed to enable the nanoscale engineering of a microenvironment for transplanted cells. The nanocoating incorporating α1-antitrypsin, an anti-inflammatory protein, exhibited effective anti-coagulant activities in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…This process approximates layer-by-layer (LBL) assembly, which has been used to create functional cell surface coatings through sequential adsorption of oppositely charged components that form thin polyelectrolyte multilayer films. This approach has been explored primarily in the modification of pancreatic islets [35][36][37] to dampen host immune reactivity and not for the intracellular delivery of therapeutics. Furthermore, previous LBL approaches have almost entirely utilized polycations to modify negatively charged cell surfaces, which is associated with significant cytotoxicity 38 .…”
Section: Discussionmentioning
confidence: 99%
“…This process approximates layer-by-layer (LBL) assembly, which has been used to create functional cell surface coatings through sequential adsorption of oppositely charged components that form thin polyelectrolyte multilayer films. This approach has been explored primarily in the modification of pancreatic islets [35][36][37] to dampen host immune reactivity and not for the intracellular delivery of therapeutics. Furthermore, previous LBL approaches have almost entirely utilized polycations to modify negatively charged cell surfaces, which is associated with significant cytotoxicity 38 .…”
Section: Discussionmentioning
confidence: 99%
“…PEG grafting could also be leveraged to tether and present bioactive agents to the host. For example, others have linked anti‐inflammatory motifs such as heparin, alpha1‐antitrypsin, urokinase, thrombomodulin, and human soluble complement receptor 1 (sCR1) with observed benefits in vitro and in rodent models . In one NHP trial, Park et al observed improved engraftment in fully immunosuppressed NHP recipients when heparin was linked to PEGylated allogenic islets .…”
Section: Discussionmentioning
confidence: 99%
“…For example, others have linked anti-inflammatory motifs such as heparin, alpha1-antitrypsin, urokinase, thrombomodulin, and human soluble complement receptor 1 (sCR1) with observed benefits in vitro and in rodent models. 41,[65][66][67][68][69] In one NHP trial, Park et al observed improved engraftment in fully immunosuppressed NHP recipients when heparin was linked to PEGylated allogenic islets. 39 Thus, bioactivity can be incorporated onto PEGylated islets in future work to impart additional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…We are therefore currently focusing on strategies that will deliver anti-inflammatory agents to the site of implantation. To do this we have applied a layer-by-layer nanoencapsulation method which can incorporate anti-inflammatory peptides such as α1-anti-trypsin ( 59 ). It is possible that this strategy combined with using insulinotropic peptides will lead to better function and survival of islets in a transplantation setting.…”
Section: Discussionmentioning
confidence: 99%